Integrated Psychological, Anesthetic, Nursing, and General Practice Approaches to the Management of Complex Regional Pain Syndrome - Hanbashi, Mousa Abdo Mansor; Hisham Mohamed Ali Moaafa,; Turki Ali Mohammed Alhuzaim ,; Basem Ali Hassan Harbi,; Fahad Mohammed Faqihi,; Aljawharah Saad Alrasheed ,; Wafa Abdullah Alolaiq ,; Ahmed Ghali Aladhab,; Dakheel Maashi D Alshammari,; Meznah Ageel Oudah Al Hazmi ,; Mohammed Saad Alhelal, (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Complex Regional Pain Syndrome (CRPS) is a debilitating chronic pain condition characterized by severe, disproportionate pain and a constellation of sensory, autonomic, motor, and trophic disturbances. It typically develops after a minor injury or surgery, with a pathophysiology involving neurogenic inflammation, peripheral and central sensitization, autonomic dysregulation, and immune system involvement. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to provide a comprehensive review of CRPS, synthesizing current evidence on its etiology, epidemiology, and the underlying pathophysiological mechanisms. Its primary focus is to outline a holistic, integrated management approach that combines medical, rehabilitative, psychological, and interventional strategies. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The study is a detailed narrative review, consolidating evidence from clinical studies, systematic reviews, and expert guidelines. It evaluates diagnostic criteria (notably the Budapest Criteria), various treatment modalities including physical therapy, pharmacotherapy, psychological interventions, and neuromodulation techniques like spinal cord stimulation. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The review finds that CRPS is a multifactorial disorder with no single curative treatment. Effective management hinges on early diagnosis and a proactive, multidisciplinary strategy. Core components include physical and occupational therapy to restore function, pharmacotherapy (e.g., corticosteroids, bisphosphonates, anticonvulsants) for symptom control, and psychological support to address pain-related distress. For refractory cases, interventional procedures such as sympathetic nerve blocks or neuromodulation can provide significant pain relief and improve quality of life. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A coordinated, interprofessional approach is fundamental to managing CRPS, offering the best opportunity to reduce pain, prevent disability, and improve patient outcomes.